(untitled) (IAHS Medical Journal, 2026)
Background: Platelet count has been used extensively to assess the severity of dengue fever, direct treatment and forecast prognosis. However, because of its exclusive use, the potential of alternative platelet indices, such as Mean Platelet Volume (MPV) has not been investigated. The association of MPV with hemorrhagic manifestations in patients with dengue fever is observed through this research. Materials and methods: This prospective observational study was conducted in a tertiary care hospital in Chattogram, Bangladesh for a period of six months. A total of 100 patients with confirmed dengue infection who fulfilled the inclusion criteria were followed from the day of admission to recovery. Clinical and laboratory findings, including platelet parameters were noted. Mann Whitney U Test was performed for correlation identification between MPV and hemorrhagic manifestations in Dengue Fever. Results: Out of 26 patients hemorrhagic manifestation. Around 50% of the patients with had a low MPV (<9fL) whereas among 74 patients without bleeding manifestation - higher MPV (>10fL) was noted in 96% of patients. A significant correlation was observed between low MPV and hemorrhagic manifestation (p value <0.001). Conclusion: Mean platelet volume has the potential to serve as an additional laboratory marker to predict hemorrhagic manifestation in patients with dengue fever. IAHS Medical Journal Vol 8(1), June 2025; 22-25